Pendidikan Multikulturalisme dan Budaya bangsa - Sanaky, Hujair AH. (Unisia, 2010)
Indonesia is plurality nation thatconsists of plurality interm of social, ethnicity, culture, religion, political party. The reality of Indonesia is called multi-cultural society. The con cept of multi-cultural is so urgent to develop and internalize in the context of the above plurality values transformation process. Because those values afore-mentioned can become the fundamental basic for plurality society as Indonesia. The best and the strategic instrument to build, socialize this concept in order to produce conducive behaviour wisely either in social or in cultural is multi-cultural education, in particular Islamic education